Dependence of gas permeation and adsorption on temperature in vacuum insulation panels (VIPs) containing getter materials. (March 2022) - Yamamoto, Hideya; Ogura, Daisuke
Vacuum insulation panels (VIPs) with a glass-fiber core has been considered to be difficult to operate for a long period of time, such as for building applications, because the thermal conductivity rises rapidly as the pressure increases. However, glass-fiber-core VIPs contain a material called a getter that continuously adsorbs permeated gas, and a theoretical model that considers the properties of the getter has not yet been developed. In this paper, the gas-adsorption mechanism by getters was investigated and a long-term-performance prediction model that considers the temperature dependence was proposed. Some gases were not adsorbed by the getter in the VIPs; however, a model was proposed that takes into account the non-absorbed gases by applying partial pressure to the adsorption isotherm in advance. The long-term performance of VIPs with different areas and volumes was compared with the measured values, and the validity of the calculation results was confirmed. These results show that the long-term performance of VIPs of different sizes can be accurately predicted when the getter performance is well understood.